2004
DOI: 10.1143/jjap.43.l818
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Phase-Change Marks Produced in Amorphous Ge2Sb2Te5 Films

Abstract: The smallest mark which can be produced in phase-change recordings has been explored using an atomic force microscope. Electrical pulses applied to amorphous Ge 2 Sb 2 Te 5 films through conducting cantilevers can produce crystalline marks, the size decreasing with decreases in input power, pulse duration, and film thickness. The smallest mark obtained is $10 nm in diameter in a film with thickness of $1 nm. Formation mechanism of the mark is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 13 publications
6
41
1
Order By: Relevance
“…We could then produce crystalline marks in amorphous Ge 2 Sb 2 Te 5 films with minimal mark diameters of ϳ10 and ϳ100 nm using an AFM and a STM. [6][7][8] similar study has been reported also by Gidon et al 11 In the present work, we will study the reverse process; that is, electrical amorphization in crystalline Ge 2 Sb 2 Te 5 films, which corresponds to the mark writing process in the present optical system. This process seems to be more difficult to be induced than the crystallization, since the amorphization occurs through rapid quenching of melted Ge 2 Sb 2 Te 5 , which is obtained above the melting temperature of ϳ600°C, 3 which is much higher than the crystallization temperature of ϳ150°C.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…We could then produce crystalline marks in amorphous Ge 2 Sb 2 Te 5 films with minimal mark diameters of ϳ10 and ϳ100 nm using an AFM and a STM. [6][7][8] similar study has been reported also by Gidon et al 11 In the present work, we will study the reverse process; that is, electrical amorphization in crystalline Ge 2 Sb 2 Te 5 films, which corresponds to the mark writing process in the present optical system. This process seems to be more difficult to be induced than the crystallization, since the amorphization occurs through rapid quenching of melted Ge 2 Sb 2 Te 5 , which is obtained above the melting temperature of ϳ600°C, 3 which is much higher than the crystallization temperature of ϳ150°C.…”
Section: Introductionsupporting
confidence: 64%
“…In previous studies, [5][6][7][8] the authors' group has demonstrated nanoscale electrical crystallization in amorphous GeSb 2 Te 4 and Ge 2 Sb 2 Te 5 films using scanning probe microscopes. In the electrical phase change, which is induced by Joule heat, 1,9,10 the mark size can be reduced using smaller electrodes, for which conducting cantilevers in atomic-force microscopes ͑AFMs͒ and metal tips in scanning-tunneling microscopes ͑STMs͒ can be utilized.…”
Section: Introductionmentioning
confidence: 99%
“…This involves determining the voltage that is required to heat the phase-change layer to the transition temperature and cause irreversible transformation in the material; this will be referred to as the threshold voltage for conduction. 2,3 When G is large and the electrical conductivity in the phase-change layer changes negligibly prior to the creation of an amorphous to crystalline transition, it can be shown that ͑4͒ may be approximated well by…”
Section: Temperature Gradientmentioning
confidence: 99%
“…These probes are used to induce semipermanent, nanoscale changes in storage media to record the binary data. One approach involved using highly conductive tips, either in contact ͑using modified atomic force microscope tips͒ [1][2][3] or in close proximity ͑using scanning tunneling microscope tips͒ 1,4,5 to a phase-change medium to deliver a current that, through Joule heating, induces stable amorphous or crystalline phase transformations to record information. Using these techniques, it was shown that it is possible to record stable crystalline marks in an amorphous material with diameters less than 50 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation